Būrhūs Frīdrīk Sīkinnir wa Ārāʾuhu fī al-Lughah - Haris Budi Cahyono (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2014)
In terms of its functions, language is regarded as a system of arbitrary vocal symbols through which members of a society communicate and cooperate with one another. It has become the primary means by which people express their thoughts, emotions, concerns, and experiences. Language is a unique characteristic that distinguishes human beings from all other creatures and is a divine gift bestowed by Allah. One of the fundamental functions of language is communication. To achieve communicative competence, individuals require language education, which is essentially a process of bringing about changes in a person's behavior, thinking, and feelings. Through this process, learners develop linguistic behavior and linguistic thinking that enable them to communicate effectively. This article discusses Burrhus Frederic Skinner as one of the linguists who laid the foundation for the behaviorist theory of second language learning. According to Skinner, language learning is the result of the interaction between stimulus and response, which is strengthened through repetition and reinforcement. Furthermore, the learning environment plays a significant role in shaping an individual's competence in acquiring a second language.